083 Response to immunosuppressive therapy in cerebral amyloid angiopathy-related inflammation. Issue 6 (24th May 2018) - Tilling, Jasmin; Trewin, Benjamin; Levy, Stanley
Abstract : Introduction: Cerebral amyloid angiopathy (CAA) is a common age-related condition characterised by amyloid beta-peptide deposition affecting the medium sized cortical and leptomeningeal arteries, arterioles and capillaries. CAA-related Inflammation (CAA-I) is an increasingly recognised variant of CAA, which is thought to be due to perivascular auto-inflammation in response to amyloid deposition. We describe the clinical course of two cases of probable CAA-I. Cases: A 71 year old man presented with new-onset seizures, headaches and subacute cognitive decline. MRI of the brain demonstrated confluent subcortical T2 white matter hyperintensities and cerebral oedema, with predominantly superimposed widespread cortico-subcortical micro-haemorrhages, in keeping with the diagnosis of CAA-I. A course of immunosuppresive therapy was commenced with five days of intravenous methylprednisolone, resulting in marked radiological and clinical improvement within two weeks. A 76 year old female presented with subacute cognitive dysfunction and apraxia, and transient left-sided weakness. MRI scan of the brain initially demonstrated a right temporo-occipital infarct, leading to primary treatment for stroke, but subsequently evolved to reveal diffuse multi-lobar T2 white matter hyperintensities with leptomeningeal involvement. A provisional diagnosis of CAA-I was made and following a poor clinical response to a trial of corticosteroid therapy, treatment with intravenous cyclophosphamide was commenced. Conclusion: These cases emphasise the importance of CAA-I as part of the differential diagnosis in patients presenting with symptoms of subacute cognitive decline, seizures, headaches and focal neurological deficits, given the potential for dramatic improvement with readily accessible immunosuppressive therapies.